(untitled) (Indian Journal of Nematology, 2024)
Fifty genotypes of bell pepper, including a control, were evaluated to unravel the source of resistance against root-knot nematode, Meloidogyne incognita Race 1. The research was conducted at Punjab Agricultural University, Ludhiana from 2021 to 2023. The preliminary screening was done in a naturally-infested polynet house and further confirmation was done in sick-plot screening, and the promising genotypes were then evaluated for horticultural traits. The results revealed that out of 50 only three genotypes, PAU SM-5, PAU SM-12 and PAU SM-32 exhibited resistant reaction, while 14 genotypes (PAU SM-6, PAU SM-16, PAU SM-20, PAU SM-21, PAU SM-27, PAU SM-28, PAU SM-30, PAU SM-45, PAU SM-71, PAU SM-78, PAU SM-98, PAU SM-100, PAU SM-101, PAU SM-102) exhibited a moderately resistant reaction against the nematode. Among others, 15 genotypes gave moderately susceptible reactions, 17 genotypes showed susceptible reactions, while the check variety PSM-1 exhibited a highly susceptible reaction to the nematodes. The genotypes PAU SM-5, PAU SM-12 and PAU SM-32 exhibited resistance, and PAU SM-27, PAU SM-28, PAU SM-30, PAU SM-45 and PAU SM-98 demonstrated moderately resistant reactions both under natural as well as sick-plot screening. Some other genotypes exhibited resistance during field screening but were found moderately susceptible or highly susceptible in the sick-plot conditions. Evaluation of promising genotypes for horticultural traits revealed a variable response among the genotypes. The genotypes showing resistant or moderately resistant reactions may be utilized to strengthen crop improvement programmes.